2018
DOI: 10.1016/j.chemer.2018.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Early Mesozoic sedimentary‒tectonic evolution of the Central-East Iranian Microcontinent: Evidence from a provenance study of the Nakhlak Group

Abstract: In Central Iran, the mixed siliciclastic-carbonate Nakhlak Group of Triassic age is commonly seen to have a Cimmerian affinity, although it shows considerable resemblances with the Triassic Aghdarband Group in far northeastern Iran, east of Kopeh-Dagh area, with Eurasian affinity. The Nakhlak Group is composed of the Alam (Late Olenekian-Anisian), Baqoroq (Late Anisian-?Early Ladinian), and Ashin (Ladinian-?Early Carnian) formations consisting mainly of volcanoclastic sandstone and shale and fossiliferous lime… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…Such subdivision has already been recognized by Alavi et al (1997). The lower part comprises first-cycle sedimentary and volcanic material as well as some recycled metamorphic basement (Hashemi Azizi et al, 2018a). The upper part comprises less sedimentary and volcanic material and is chiefly composed of low-grade metamorphic detritus (Zanchi et al, 2009b;Hashemi Azizi et al, 2018a).…”
Section: Geological Settingmentioning
confidence: 85%
See 4 more Smart Citations
“…Such subdivision has already been recognized by Alavi et al (1997). The lower part comprises first-cycle sedimentary and volcanic material as well as some recycled metamorphic basement (Hashemi Azizi et al, 2018a). The upper part comprises less sedimentary and volcanic material and is chiefly composed of low-grade metamorphic detritus (Zanchi et al, 2009b;Hashemi Azizi et al, 2018a).…”
Section: Geological Settingmentioning
confidence: 85%
“…Petrographic analysis of thin sections (i.e. modal analysis via point counting) revealed that most of the sandstone samples from the Alam Formation include dominantly volcanic detritus mainly represented by lithic fragments and single phenocrysts such as volcanic quartz grains and feldspars (Hashemi Azizi et al, 2018a). The average total quartz-feldspar-lithic fragment ratio is Qt21.6:F38.7:L39.7 (Hashemi Azizi et al, 2018a).…”
Section: Geological Settingmentioning
confidence: 99%
See 3 more Smart Citations